Cooperative Inversion of Magnetotelluric and Seismic Data - Le, Van Anh Cuong (Curtin University, 2017)
Cooperative inversion is the beneficial transference of information from one geophysical technique to another for improving the recovery of subsurface rock properties. The research’s focus is the development and comparison of new strategies for cooperatively inverting seismic and magnetotelluric data. This is intended to improve the recovery of subsurface electrical conductivity. The developed techniques are applied to two industry scale case sites containing large co-located seismic and MT surveys.